Predictive Analytics in Marketing: Contribution to Marketing Performance - Muhajir, Ali (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This systematic literature review explores predictive analytics in marketing decision making and its relationship to key concepts in consumer behavior prediction. Drawing on established theories and empirical studies, this study explores the influence of customer-based brand equity, brand attachment, self-concept, perceived value, and other variables on consumer purchasing behavior and intentions. Additionally, this study investigates the impact of social psychology theory, destination image, sustainability in marketing, and marketing practices that align with consumer values ​​on satisfaction, engagement, loyalty, and long-term relationships with brands. Apart from that, this study also tests the effectiveness of predictive marketing algorithms in improving marketing and sales performance. These findings emphasize the importance of integrating consumer-centric approaches and predictive analytics in forming successful marketing strategies and achieving desired results in today's competitive market landscape.